Cloth, method for producing the same, and clothing made thereof

By adding infrared absorbent to the acrylic fiber and combining the cellulose fiber, and then performing multi-layer fluorescence dyeing, the problem of difficult to take into account both arc resistance and high visibility in the prior art is solved, and efficient arc protection and light resistance are achieved.

CN115955924BActive Publication Date: 2025-04-29KANEKA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202180051423.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-16
Filing Date
2021-05-26
Publication Date
2025-04-29
Estimated Expiration
2041-05-26

AI Technical Summary

Technical Problem

In the prior art, arc resistance and high visibility of acrylic fibers are difficult to take into account, and light fastness and friction fastness after dyeing are insufficient.

Method used

The acrylic fiber containing an infrared absorber is combined with the cellulose fiber, and the multi-layer dyeing of cationic dyes, reactive dyes and dispersed dyes are formed to form a fluorescent yellow cloth.

Benefits of technology

The fabric has high arc resistance, visibility and friction fastness, ensuring that the material has good protective performance when exposed to arc environment, and the color remains unchanged after light resistance test.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004087254800000151
    Figure BDA0004087254800000151
  • Figure BDA0004087254800000161
    Figure BDA0004087254800000161
  • Figure BDA0004087254800000162
    Figure BDA0004087254800000162
Patent Text Reader

Abstract

The present invention relates to a fabric containing acrylic fiber A and cellulose fiber, wherein the acrylic fiber A contains an infrared absorber inside the fiber, and the fabric is dyed with at least a yellow cationic dye, a yellow reactive dye, and a yellow disperse dye. The fabric can be produced by dyeing the fabric containing acrylic fiber A and cellulose fiber into fluorescent yellow using a cationic dye, a reactive dye, and a disperse dye. Thus, a fabric having excellent arc resistance and visibility, a method for producing the fabric, and clothing using the fabric can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cloth containing acrylic fibers and having arc resistance and high visibility, a method for producing the cloth, and clothing using the cloth. Background Art

[0002] In recent years, many accidents caused by arc flash have been reported. In order to prevent the danger of arc flash, the clothes worn by workers such as electricians and factory workers who work in an environment with the danger of being exposed to arcs are required to be arc-resistant. For example, Patent Document 1 describes a fabric for arc protective clothing containing acrylic fibers, which contain an infrared absorber. In addition, it is desired that the arc protective clothing has high visibility that makes it easy for other people to find the worker. For example, Patent Document 2 describes dyeing fibers or fabrics in order to give visibility to flame-retardant fabrics containing synthetic cellulose fibers, modified polyacrylonitrile fibers, and para-aramid fibers used in protective clothing.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: International Publication No. 2016 / 111116

[0006] Patent Document 2: Japanese Patent Application No. 2010-502849 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] However, the inventors found that the acrylic fiber described in Patent Document 1 has a blue color due to the infrared absorber. If it is dyed into fluorescent yellow (also called fluorescent yellow) for the purpose of high visibility like ordinary acrylic fibers, it sometimes becomes fluorescent green, especially after the xenon light fastness test, it is easy to become fluorescent green (low light fastness). In addition, in Patent Document 2, the performance of arc resistance is controlled by adjusting the amount of para-aramid fiber. If the amount of para-aramid fiber increases, the arc resistance is improved, but there is a problem of hardening the fabric. If the amount of para-aramid fiber is small, there is a problem of reduced arc resistance. On the other hand, from the perspective of imparting visibility, synthetic cellulose and modified polyacrylonitrile fibers can be used, but in order to bring about high visibility, the amount of these fibers needs to be increased, and there is still room for improvement from the perspective of taking into account arc resistance. In addition, in the method of post-processing (such as printing) the fabric to obtain high visibility, there are still problems from the perspective of durability (such as friction fastness).

[0009] The present invention solves the above-mentioned conventional problems and can provide a cloth having arc resistance, high visibility and excellent fastness, a method for producing the cloth, and clothing using the cloth.

[0010] Means for solving problems

[0011] The present invention relates to a fabric containing acrylic fibers, characterized in that: in one or more embodiments, the fabric contains acrylic fibers A and cellulose fibers, and the fabric is dyed with at least a cationic dye, a reactive dye, and a disperse dye, and the cationic dye, reactive dye, and disperse dye are all yellow fluorescent dyes.

[0012] The present invention relates to clothing material, characterized in that, in one or more embodiments, the clothing material comprises the above-mentioned fabric.

[0013] The present invention relates to a method for manufacturing a fabric. In one or more embodiments, the method is characterized in that a fabric containing acrylic fiber A and cellulose fiber is dyed with a cationic dye, a reactive dye, and a disperse dye, and the cationic dye, the reactive dye, and the disperse dye are all yellow fluorescent dyes.

[0014] Effects of the Invention

[0015] According to the present invention, it is possible to provide a cloth having arc resistance, high visibility and excellent fastness, a method for producing the cloth, and clothing using the cloth. DETAILED DESCRIPTION

[0016] The inventors of the present invention have conducted intensive research and found that by dyeing a fabric made of acrylic fiber and cellulose fiber containing an infrared absorber with a predetermined dye, a fabric having arc resistance and high visibility can be provided, and the fabric has excellent fastness.

[0017] <Arc resistance>

[0018] Arc resistance can be evaluated by ATPV (Arc Thermal Performance Value), which can be measured by an arc test based on standard ASTM F1959 / F1959M-12 (Standard Test Method for Determining the Arc Rating of Materials for Clothing).

[0019] The fabric of one or more embodiments of the present invention has a basis weight (weight (ounce) of the fabric per unit area (1 square yard)) of 6.5 oz / yd.2 When the ATPV measured based on ASTM F1959 / F1959M-12 is less than 8 cal / cm 2 above.

[0020] The fabric of one or more embodiments of the present invention preferably has a weight per unit area of ​​3 to 10 oz / yd from the viewpoint of arc resistance and light weight. 2 , more preferably 4 to 9 oz / yd 2 , more preferably 4 to 8 oz / yd 2 As long as the weight per unit area is within the above range, a lightweight clothing material with excellent workability can be obtained.

[0021] In addition, in this specification, the range expressed by "... to..." is the same as the range expressed by "... or more and... or less".

[0022] <Visibility>

[0023] In one or more embodiments of the present invention, the so-called "high visibility" means that the color is fluorescent yellow and meets the standard of "5.1 Requirements for color" of "ISO20471:2013". In addition, the light fastness is high and "high visibility" is shown even after the xenon light fastness test. Specifically, it is fluorescent yellow even after the xenon light fastness test and meets the standard of "5.2 Requirements for color after the xenon light fastness test" of "ISO 20471:2013". That is, both standards mean that the color coordinates (x, y) are within the range of (0.387, 0.610) (0.356, 0.494) (0.398, 0.452) (0.460, 0.540) (fluorescent yellow), and the brightness rate β is 0.70 or more.

[0024] In the fabric of one or more embodiments of the present invention, high visibility can be obtained by dyeing with a prescribed dye. When a conventional acrylic fiber is dyed with a yellow dye so as to exhibit fluorescent yellow due to its white color, a desired color can be obtained, but the acrylic fiber A has a blue color due to its infrared absorber, and if it is dyed with a yellow dye so as to exhibit fluorescent yellow for the purpose of high visibility, it may become fluorescent green. Therefore, by forming a fabric with acrylic fiber A and a cellulose fiber together, and dyeing with a prescribed yellow dye described later, a fabric with high visibility that meets the standards 5.1 and 5.2 of "ISO 20471:2013" can be obtained. In addition, since a colorant is not attached to the fabric by post-processing, the rubbing fastness is not impaired.

[0025] <Dyeing>

[0026] In order to obtain a fabric that exhibits fluorescent yellow, especially after a light resistance test, cationic dyeing, reactive dyeing, and disperse dyeing are performed as three dyeing methods. The dyeing order of cationic dyeing, reactive dyeing, and disperse dyeing is not particularly limited, and dyeing can also be performed by a three-bath dyeing method or a two-bath dyeing method. For example, the order of first performing cationic dyeing, then reactive dyeing, and finally disperse dyeing can be cited. The temperature during dyeing is preferably 30°C to 100°C, and more preferably 35°C to 98°C. In addition, the holding time at this temperature is preferably 1 minute to 180 minutes, and more preferably 5 minutes to 150 minutes.

[0027] The so-called cationic dyeing is a method commonly used as a dyeing method for acrylic fibers. As the cationic dye, there is no particular limitation as long as it is a yellow fluorescent dye, and for example, Astrazon Flavine 10GFE 300%, Astrazon Yellow 8GSL200%, and Astrazon Yellow 7GLL200% manufactured by Dystar can also be used. The cationic dye can be used alone or in combination of two or more.

[0028] Reaction dyeing refers to a dyeing method in which a functional group such as a hydroxyl group, an amino group, an amide group or a carboxyl group of a fiber to be dyed such as a cellulose fiber reacts chemically with a triazine chloride or an ethyl sulfonate of a reaction dye to dye the fiber through a covalent bond. The reaction dye is not particularly limited as long as it is a yellow fluorescent dye, and for example, Remazol Luminus YELLOW FL, Remazol Yellow GG 150%, and Remazol Yellow GL 150% manufactured by Dystar can be used. The reaction dye can be used alone or in combination of two or more.

[0029] Disperse dyeing refers to a method of physically dyeing fibers by dispersing water-insoluble disperse dyes in water. Disperse dyes are not particularly limited as long as they are yellow fluorescent dyes, and for example, Terasil Flavine 10GFF, Dianix Yellow AC-E, and Dianix Yellow UN-SE manufactured by Dystar can be used. Disperse dyes can be used alone or in combination of two or more.

[0030] Furthermore, within the range that does not adversely affect dyeing, dyeing auxiliaries such as fluorescent brighteners, dyeing accelerators, pH adjusters, and leveling agents may be used together with the dye.

[0031] Fluorescent whitening agents are dyes that absorb ultraviolet light and emit fluorescence at 400 to 450 nm. Fluorescent whitening agents complement the yellow absorption portion and increase reflection, making the color look brighter. The fluorescent whitening agent is not particularly limited, and Uvitex AC LIQ manufactured by HUNTSMAN can be used.

[0032] The dyeing accelerator is a chemical that makes the fiber swell so that the dye or chemical can easily enter the fiber, and is used to facilitate dyeing. The dyeing accelerator is not particularly limited, and for example, TANAVOL-DAP (manufactured by TANATEX) can be used.

[0033] The pH adjuster is used for adjusting the pH, and is not particularly limited. For example, Ultra MT110 (manufactured by Midei Chemical Co., Ltd.) can be used.

[0034] The leveling agent is an auxiliary agent used to uniformly dye the fabric in order to prevent uneven dyeing. The leveling agent is not particularly limited, and for example, INVALON NA (manufactured by HUNTSMAN) can be used.

[0035] Furthermore, from the viewpoint of improving physical properties and dyeing properties, sodium salts such as sodium nitrate and sodium carbonate, calcium salts, and alkali salts may be added to the extent that dyeing is not adversely affected.

[0036] In addition, the dyed fabric may be bleached to improve whiteness, and the bleaching agent is not particularly limited, and for example, Nichilon White WX Liquid (manufactured by Nissei Chemicals Co., Ltd.) can be used. However, if the fabric is bleached before dyeing, it is difficult to obtain the desired fluorescent yellow, so it is not preferred.

[0037] In one or more embodiments of the present invention, when the above three dyes are used to dye the fabric, the dye used in the dyeing can be confirmed by, for example, the following method. The fabric to be dyed is immersed in pyridine to extract the dye. Furthermore, if the dye is extracted, the pyridine becomes yellow due to the dissolution of the dye in the pyridine. When it is confirmed that the dye is extracted, the fabric is dyed with any one of a fluorescent yellow disperse dye, a fluorescent yellow cationic dye, and a fluorescent yellow reactive dye. Next, toluene and water are added to the extracted dye, and the mixture is separated into two layers by vibrating. Thus, the upper layer (toluene layer) contains the disperse dye, and the lower layer (water layer) contains the cationic dye and the reactive dye. The toluene layer of the upper layer is extracted, and the liquid is concentrated. The presence or absence of the disperse dye can be identified by JIS L1065.

[0038] <Fastness>

[0039] Fastness is an index to measure the resistance of fabrics dyed with dyes, etc. It is an index of the ease of discoloration and fading of the fabric's color, and the test method is determined in the JIS standard. Generally, the value of fastness is expressed on a half-grade scale from 1 to 5, which means that the larger the value of the grade, the better the fastness, and the smaller the value, the worse.

[0040] The fabric of one or more embodiments of the present invention has excellent fastness to rubbing fastness in addition to light fastness by dyeing as described above, so it is excellent in durability even when used as clothing. The fabric preferably has a rubbing fastness of 4.5 or more in a dry test measured by the rubbing fastness test method specified in JIS L0849, and a rubbing fastness of 3.5 or more in a wet test.

[0041] <Acrylic Fiber A>

[0042] In one or more embodiments of the present invention, the acrylic fiber A contains an infrared absorber inside the fiber. By containing an infrared absorber in the acrylic fiber A, the reflection and / or absorption of light can be adjusted, arc performance is given to the acrylic fiber A, and further, the fabric containing the acrylic fiber A has arc resistance. Arc resistance can be measured as described above. In addition, by containing an infrared absorber, the acrylic fiber A has a higher infrared absorption energy, and a fabric with a heat shielding rate of less than 40% can be obtained. The so-called heat shielding rate is a value obtained by evaluating the fabric based on a generally known heat shielding test. From the viewpoint of taking into account arc resistance, infrared absorption function and spinnability, it is preferred that the acrylic fiber A contains an infrared absorber at a rate of 1% by weight or more and 30% by weight or less relative to the total weight of the acrylic fiber. From the viewpoint of improving arc resistance and infrared absorption function, it is preferred that the acrylic fiber A contains an infrared absorber at a rate of 2% by weight or more relative to the total weight of the acrylic fiber, more preferably 3% by weight or more, and particularly preferably 4% by weight or more. From the viewpoint of spinnability, the infrared absorber is more preferably contained in an amount of 20% by weight or less, further preferably 15% by weight or less, and particularly preferably 10% by weight or less, based on the total weight of the acrylic fiber.

[0043] In addition, in acrylic fiber A, the infrared absorber exists inside the acrylic fiber, so the hand feeling is better than when the infrared absorber is attached to the fiber surface, and the fastness is also high. Since the infrared absorber is added and mixed in the spinning solution before spinning, the infrared absorber is easily and evenly dispersed in the obtained fiber, and there is no need to use an adhesive for dispersion, so the hand feeling is not impaired. On the other hand, when the infrared absorber is attached to the fiber surface, it is difficult to penetrate into the inside because it is applied to the fiber and fabric through post-processing such as printing, and it is easy to attach to the surface more and fall off easily. In addition, since an adhesive is used for attachment, the obtained fiber and fabric tend to be hard and have a poor hand feeling.

[0044] From the viewpoints of spinnability, cost, and uniformity of arc resistance, it is preferred that the acrylic fiber A is a single fiber and the infrared absorber is dispersed throughout the fiber.

[0045] The infrared absorber is not particularly limited as long as it has an infrared absorption effect. For example, it is preferred to have an absorption peak in the wavelength region of 750 to 2500 nm. Specifically, antimony-doped tin oxide, indium tin oxide, niobium-doped tin oxide, phosphorus-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide supported on a titanium oxide substrate, iron-doped titanium oxide, carbon-doped titanium oxide, fluorine-doped titanium oxide, nitrogen-doped titanium oxide, aluminum-doped zinc oxide, antimony-doped zinc oxide, etc. can be cited. Indium tin oxide includes indium-doped tin oxide and tin-doped indium oxide. From the viewpoint of improving arc resistance and infrared absorption energy, the infrared absorber is preferably a tin oxide compound, and more preferably one or more selected from antimony-doped tin oxide, indium tin oxide, niobium-doped tin oxide, phosphorus-doped tin oxide, and fluorine-doped tin oxide. In addition, if the above-mentioned infrared absorber is used, arc resistance and infrared absorption energy can be improved, and acrylic fibers can be formed into a light color, so it is preferred. The above-mentioned infrared absorber can be used alone or in combination of two or more.

[0046] The particle size of the infrared absorber is preferably 2 μm or less, more preferably 1 μm or less, and further preferably 0.5 μm or less, from the viewpoint of being easily dispersed in the acrylic polymer constituting the acrylic fiber A. In the present invention, the particle size of the infrared absorber can be measured by laser diffraction when it is a powder, and can be measured by laser diffraction or dynamic light scattering when it is a dispersion (dispersion liquid) dispersed in water or an organic solvent.

[0047] The acrylic fiber A may contain a flame retardant, a flame retardant auxiliary, or a light diffusing and reflecting substance in addition to the infrared absorber.

[0048] There is no particular limitation on the flame retardant, and examples thereof include antimony compounds. The content of the flame retardant in the acrylic fiber A is preferably 1 to 30% by weight, and more preferably 2 to 20% by weight, relative to the total weight of the fiber. As long as the content of the antimony compound in the acrylic fiber A is within the above range, the production stability in the spinning process is excellent, and the flame retardancy is also good. Examples of the antimony compound include antimony trioxide, antimony tetroxide, antimony pentoxide, antimony acid, antimony salts such as sodium antimonate, antimony oxychloride, and the like, and one or more of them can be used in combination. From the perspective of production stability in the spinning process, the antimony compound is preferably one or more compounds selected from antimony trioxide, antimony tetroxide, and antimony pentoxide.

[0049] Since the light-diffusing reflective material absorbs light in the ultraviolet region in addition to the infrared region, the arc resistance of the fabric is further improved by containing the light-diffusing reflective material. As the above-mentioned light-diffusing reflective material, there is no particular limitation, for example, inorganic compounds such as titanium oxide and zinc oxide, triazine compounds, benzophenone compounds, benzotriazole compounds and other organic compounds can be used. Among them, titanium oxide is preferred from the viewpoint of coloring. The acrylic fiber A preferably contains the light-diffusing reflective material at 0.3 to 10 weight % relative to the total weight of the acrylic fiber, more preferably 0.5 to 7 weight %, and further preferably 1 to 5 weight %. According to this range, arc resistance can be improved, and the feel is also good.

[0050] From the viewpoint of being easily dispersed in the acrylic polymer constituting the acrylic fiber A, the particle size of the light-diffusing reflective substance is preferably 2 μm or less, more preferably 1.5 μm or less, and further preferably 1 μm or less. In addition, in the case of titanium oxide, the particle size is preferably 0.4 μm or less, and more preferably 0.2 μm or less. Regarding organic light-diffusing reflective substances, which are compounds dissolved in an organic solvent used in the manufacture of spinning stock solutions, the particle size is not limited. In the present invention, the particle size of the light-diffusing reflective substance can be measured by a laser diffraction method when it is a powder, and can be measured by a laser diffraction method or a dynamic light scattering method when it is a dispersion dispersed in water or an organic solvent.

[0051] Furthermore, various additives such as a matting agent, a crystal nucleating agent, a dispersant, a lubricant, a stabilizer, a fluorescent agent, an antioxidant, an antistatic agent, and a pigment may be contained as necessary within a range not hindering the purpose of the present invention.

[0052] Preferably, the acrylic fiber A is formed of an acrylic polymer containing 40 to 70% by weight of acrylonitrile and 30 to 60% by weight of other components relative to the total weight of the acrylic polymer. As long as the content of acrylonitrile in the acrylic polymer is 40 to 70% by weight, the heat resistance and flame retardancy of the acrylic fiber are good.

[0053] The other components are not particularly limited as long as they are copolymerizable with acrylonitrile, and examples thereof include halogen-containing vinyl monomers and sulfonic acid group-containing monomers.

[0054] Examples of the halogen-containing vinyl monomers include halogen-containing vinyls and halogen-containing vinylidene monomers. Examples of the halogen-containing vinyls include vinyl chloride and vinyl bromide. Examples of the halogen-containing vinylidene monomers include vinylidene chloride and vinylidene bromide. These halogen-containing vinyl monomers may be used alone or in combination of two or more. From the viewpoint of heat resistance and flame retardancy, the arc-resistant acrylic fiber preferably contains 30 to 60% by weight of a halogen-containing vinyl monomer as another component relative to the total weight of the acrylic polymer.

[0055] As the above-mentioned sulfonic acid group-containing monomer, for example, methallyl sulfonic acid, allyl sulfonic acid, styrene sulfonic acid, 2-acrylamide-2-methylpropane sulfonic acid and their salts can be listed. Among the above, as salts, for example, sodium salts, potassium salts, ammonium salts, etc. such as p-styrene sodium sulfonate can be listed, but it is not limited to these. These sulfonic acid group-containing monomers can be used alone or in combination of two or more. The sulfonic acid group-containing monomer can be used as needed, for example, the content of the sulfonic acid group-containing monomer in the acrylic polymer can also be 0.5% by weight or more. As long as the content of the sulfonic acid group-containing monomer in the above-mentioned acrylic polymer is 3% by weight or less, the production stability of the spinning process is excellent.

[0056] Preferably, the acrylic polymer is a copolymer containing 40 to 70% by weight of acrylonitrile, 30 to 57% by weight of a halogen-containing vinyl monomer, and 0 to 3% by weight of a sulfonic acid group-containing monomer. More preferably, the acrylic polymer is a copolymer containing 45 to 65% by weight of acrylonitrile, 35 to 52% by weight of a halogen-containing vinyl monomer, and 0 to 3% by weight of a sulfonic acid group-containing monomer. Further preferably, the acrylic polymer is a copolymer containing 45 to 65% by weight of acrylonitrile, 34.5 to 52% by weight of a halogen-containing vinyl monomer, and 0.5 to 3% by weight of a sulfonic acid group-containing monomer.

[0057] The fineness of the acrylic fiber A is not particularly limited, but is preferably 1 to 20 dtex, more preferably 1.5 to 15 dtex, from the viewpoints of spinnability, processability, and the feel and strength of a woven fabric and / or knitted fabric. In addition, the fiber length of the acrylic fiber A is not particularly limited, but is preferably 38 to 127 mm, more preferably 38 to 76 mm, from the viewpoints of spinnability and processability. In the present invention, the fineness of the fiber is measured based on JIS L1015.

[0058] The strength of the acrylic fiber A is not particularly limited, but is preferably 1.0 to 4.0 cN / dtex, more preferably 1.5 to 3.0 cN / dtex, from the viewpoint of spinnability and processability. The elongation of the acrylic fiber A is not particularly limited, but is preferably 20 to 35%, more preferably 20 to 25%, from the viewpoint of spinnability and processability. In the present invention, the strength and elongation of the fiber are measured based on JIS L1015.

[0059] The acrylic fiber can be produced by wet spinning the spinning solution in the same manner as in the case of general acrylic fibers, except that an infrared absorber and a light diffusing reflective substance are added to the spinning solution in which the acrylic polymer is dissolved.

[0060] The fabric of one or more embodiments of the present invention preferably contains 30 to 70% by weight of acrylic fiber relative to the total weight of the fabric, more preferably 30 to 65% by weight, and even more preferably 35 to 55% by weight. If the content of acrylic fiber in the fabric is within the above range, excellent flame retardancy and hand feel can be imparted.

[0061] <Cellulose Fiber>

[0062] In one or more embodiments of the present invention, the fabric contains cellulose fibers. The visibility based on dyeing is improved, and the feel is good. There is no particular limitation as cellulose fibers. For example, as natural cellulose fibers, cotton, kapok, linen, ramie, jute, etc. can be used. In addition, the above-mentioned natural cellulose fibers can also be flame-retarded cellulose fibers in which natural cellulose fibers such as cotton, kapok, linen, ramie, jute, etc. are flame-retarded by flame retardants such as phosphorus compounds such as N-hydroxymethylphosphonate compounds and tetrahydroxyalkylphosphonium salts. As synthetic cellulose fibers, regenerated fibers such as viscose rayon and cuprammonium fibers can be used. In addition, the above-mentioned synthetic cellulose fibers can also be flame-retarded synthetic cellulose fibers in which regenerated fibers such as viscose rayon and cuprammonium fibers are flame-retarded by flame retardants such as N-hydroxymethylphosphonate compounds and tetrahydroxyalkylphosphonium salts.

[0063] These cellulose fibers may be used alone or in combination of two or more. From the viewpoint of strength, the fiber length of the cellulose fibers is preferably 15 to 51 mm, more preferably 20 to 38 mm.

[0064] In the fabric of one or more embodiments of the present invention, the cellulose fiber is preferably contained in an amount of 40 to 65% by weight, more preferably 30 to 60% by weight, and even more preferably 35 to 55% by weight relative to the total weight of the fabric. If the content of the cellulose fiber in the fabric is within the above range, the fabric can be provided with excellent hand feel and hygroscopicity, and the durability of the fabric can be improved.

[0065] Specifically, the fabric of one or more embodiments of the present invention preferably contains 30 to 70% by weight of acrylic fiber A and 30 to 70% by weight of cellulose fiber, more preferably 30 to 65% by weight of acrylic fiber A and 35 to 70% by weight of cellulose fiber, further preferably 35 to 60% by weight of acrylic fiber A and 40 to 65% by weight of cellulose fiber, and particularly preferably 35 to 55% by weight of acrylic fiber A and 45 to 65% by weight of cellulose fiber, relative to the total weight of the fabric.

[0066] <Other Fibers>

[0067] In one or more embodiments of the present invention, the fabric may further contain aromatic polyamide fibers from the viewpoint of improving the durability of the fabric. The aromatic polyamide fibers may be contained in an amount of 5 to 30% by weight, 5 to 25% by weight, 3 to 25% by weight, or 1 to 20% by weight relative to the total weight of the fabric.

[0068] Specifically, the fabric of one or more embodiments of the present invention may contain 30 to 65% by weight of acrylic fiber A, 30 to 65% by weight of cellulose fiber and 5 to 30% by weight of aromatic polyamide, 35 to 60% by weight of acrylic fiber A, 35 to 60% by weight of cellulose fiber and 5 to 25% by weight of aromatic polyamide fiber, 35 to 57% by weight of acrylic fiber A, 40 to 62% by weight of cellulose fiber and 3 to 25% by weight of aromatic polyamide fiber, or 35 to 54% by weight of acrylic fiber A, 45 to 64% by weight of cellulose fiber and 1 to 20% by weight of aromatic polyamide fiber, relative to the total weight of the fabric.

[0069] The aromatic polyamide fiber may be a para-aromatic polyamide fiber or a meta-aromatic polyamide fiber. The fineness of the aromatic polyamide fiber is not particularly limited, but from the viewpoint of strength, it is preferably 1 to 20 dtex, and more preferably 1.5 to 15 dtex. In addition, the fiber length of the aromatic polyamide fiber is not particularly limited, but from the viewpoint of strength, it is preferably 35 to 127 mm, and more preferably 38 to 76 mm.

[0070] Furthermore, in one or more embodiments of the present invention, in addition to the above-mentioned fibers, other chemical fibers such as natural fibers, polyimide fibers, and polyester fibers may be contained within a range that does not hinder the purpose of the present invention.

[0071] <Cloth>

[0072] In the fabric of one or more embodiments of the present invention, the fiber may be a staple yarn or a filament. They can be appropriately selected according to the purpose. Regarding the fiber, for example, a fiber mixture containing acrylic fiber A can be spun by a known spinning method. Examples of the spinning method include ring spinning, air spinning, and air jet spinning, but are not limited to these spinning methods.

[0073] There is no particular limitation on the fabric, for example, woven fabrics, knitted fabrics, non-woven fabrics, etc. can be listed. In addition, it can also be an interwoven fabric or an interwoven knitted fabric. The structure of the fabric is not particularly limited, and it can be the three basic structures such as plain weave, twill, and satin, or it can be a modified application structure using special looms such as multi-arm looms or jacquard looms. The structure of the knitted fabric is also not particularly limited, and it can be any of circular weaving, weft knitting, and warp knitting. The above-mentioned fabric can also be a mesh cloth (fabric) using two or more yarns as the warp yarn and two or more yarns as the weft yarn. There is no particular limitation on the method of making the non-woven fabric, and it can be any of thermal bonding, chemical bonding, needle punching, etc.

[0074] <Material>

[0075] In one or more embodiments of the present invention, clothing materials include ordinary loose jackets, short jackets, going out clothes, vests, windbreakers, cold-proof clothing, coats, raincoats, shirts, sportswear, gloves, hats and shoes, as well as work clothes or firefighting clothes for workers on general roads, dedicated roads for automobiles, ports, airports, railways, parking lots, oil fields, gas fields, comprehensive chemical plants, power-related departments, etc., but are not particularly limited to these.

[0076] Furthermore, the part of the clothing material using the fabric of one or more embodiments of the present invention may be the entire clothing material or a part thereof. When the fabric of one or more embodiments of the present invention is used in a part of the clothing material, it may be used in a part of the clothing material in a pattern such as stripes, or may be used in the entire part of the clothing material such as sleeves, lapels, hems, etc. Furthermore, it is preferred that the entire outer side of the clothing material is formed by the fabric of the present embodiment.

[0077] When the fabric of one or more embodiments of the present invention is used for a striped pattern, the width of the stripes is not particularly limited, but from the viewpoint of high visibility, it is preferably 50 mm or more. In addition, when the fabric of one or more embodiments of the present invention is used as a garment, it is preferably used across the front and back of the garment. For example, it is preferably used continuously from the front to the back.

[0078] The area occupied by the fabric according to one or more embodiments of the present invention in the clothing is not particularly limited in the outer portion of the clothing, but is preferably 0.14 m 2 More preferably 0.5m 2 More preferably, 0.8 m 2 It is particularly preferred that all clothing materials be manufactured using the fabric according to one or more embodiments of the present invention.

[0079] Furthermore, the fabric in one or more embodiments of the present invention is not limited to clothing, and can also be used for tents, awnings, flags, and the like.

[0080] Example

[0081] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples.

[0082] First, the measurement method and the evaluation method are described.

[0083] (Visibility)

[0084] [Confirmation of compliance with "5.1 Colorimetric requirements" of "ISO 20471:2013"]

[0085] According to 5.1 of ISO 20471:2013, a spectrophotometer (CM-2500C (manufactured by Konica Minolta Inc.)) was used to measure Y, x, and y in the Yxy colorimetric system to determine whether the fluorescent yellow range was met. In addition, the brightness ratio β was calculated as β=Y / 100, and β≥0.7 was considered acceptable.

[0086] The compliance criteria are shown in Table 1 below.

[0087] [Confirmation of compliance with "5.2 Requirements for color after xenon light fastness test" of "ISO 20471:2013" (light fastness)]

[0088] According to ISO 20471:2013, 5.2, color requirements after xenon light fastness test, after xenon light fastness test, Y, x, y of Yxy color system were measured by using spectrophotometer (CM-2500C (manufactured by Konica Minolta Co., Ltd.) to determine whether the range of fluorescent yellow was met. In addition, the brightness ratio β was calculated according to β=Y / 100. The compliance criteria were the same as those in Table 1.

[0089] (ATPV)

[0090] The arc test is conducted based on ASTM F1959 / F1959M-12 (Standard Test Method for Determining the Arc Rating of Materials for Clothing) to obtain ATPV (cal / cm 2 ).

[0091] (Rubbing fastness)

[0092] The friction fastness test is carried out using a friction tester based on the friction fastness test method specified in JIS L0849. The test piece and the friction white cotton cloth are rubbed against each other, and the degree of coloration of the friction white cotton cloth is compared with the gray scale for contamination to determine the friction fastness in the dry test and the wet test.

[0093] <Production Example 1>

[0094] An acrylic copolymer containing 51% by weight of acrylonitrile, 48% by weight of vinylidene chloride and 1% by weight of sodium p-styrene sulfonate is dissolved in dimethylformamide in such a manner that the resin concentration reaches 30% by weight. To the obtained resin solution, 10 parts by weight of antimony trioxide (Sb2O3, manufactured by Nippon Seiko Co., Ltd., product name "Patx-M") is added to 100 parts by weight of the resin as a spinning solution. The above antimony trioxide is added in advance in such a manner that it reaches 30% by weight relative to dimethylformamide, and is evenly dispersed, and used as a modulated dispersion. In the above antimony trioxide dispersion, the particle size of the antimony trioxide measured by laser diffraction is less than 2 μm. The obtained spinning solution was extruded into a 50 wt% dimethylformamide aqueous solution using a nozzle having a nozzle hole diameter of 0.08 mm and a number of holes of 300 holes, and coagulated, followed by washing with water and drying at 120°C, and after drying, stretched to 3 times, and then heat-treated at 145°C for 5 minutes to obtain acrylic fibers. The acrylic fibers had a fineness of 1.71 dtex, a strength of 2.58 cN / dtex, an elongation of 27.4%, and a cut length of 51 mm. The fineness, strength, and elongation of the fibers were measured in accordance with JIS L1015.

[0095] <Production Example 2>

[0096] To the resin solution obtained above, 10 parts by weight of antimony trioxide (Sb2O3, manufactured by Nippon Seiko Co., Ltd., product name "Patx-M") and 10 parts by weight of antimony-doped tin oxide (manufactured by Ishihara Sangyo Co., Ltd., product name "SN-100P") are added relative to 100 parts by weight of the resin to form a spinning solution. The antimony trioxide is added in advance in a manner to reach 30% by weight relative to dimethylformamide, and is evenly dispersed, and used as a modulated dispersion. In the antimony trioxide dispersion, the particle size of antimony trioxide measured by laser diffraction is less than 2 μm. The antimony-doped tin oxide is added in advance in a manner to reach 30% by weight relative to dimethylformamide, and is evenly dispersed, and used as a modulated dispersion. In the antimony trioxide dispersion, the particle size of antimony trioxide measured by laser diffraction is 0.01 to 0.03 μm. The obtained spinning solution was extruded into a 50 wt% dimethylformamide aqueous solution using a nozzle having a nozzle hole diameter of 0.08 mm and a hole number of 300 holes, and coagulated, and then washed with water and dried at 120°C, and after drying, stretched to 3 times, and then heat-treated at 145°C for 5 minutes, thereby obtaining acrylic fiber A containing an infrared absorber. The obtained acrylic fiber A had a fineness of 1.7 dtex, a strength of 2.5 cN / dtex, an elongation of 26%, and a cut length of 51 mm.

[0097] (Example 1)

[0098] The acrylic fiber A of manufacturing example 2: 32 wt%, lyocell fiber: 51 wt% (manufactured by Lenzing, trade name "Tencel", fineness 1.3 dtex, fiber length 38 mm), aromatic polyamide fiber: 10 wt% (manufactured by DuPont, trade name "Kever", fineness 1.7 dtex, fiber length 51 mm) and acrylic fiber of manufacturing example 1: 7 wt% are mixed and spun by ring spinning. The obtained staple yarn is a blended yarn with a British cotton yarn count of 20 count. The staple yarn is used to make a twill fabric (cloth) using a conventional spinning method. The obtained cloth (weight per unit area 5.7 oz / yd 2 ), and then the dyeing steps (1) to (3) described later are carried out to obtain a fabric dyed in fluorescent yellow.

[0099] (1) After the fabric was cation-dyed at 98°C for 60 minutes, it was washed with water and hot water (warm water at 20 to 40°C). In the dyeing, a dye solution containing 2% by weight of Astrazon Flavine 10GFE300% (manufactured by Dystar), 4% by weight of Uvitex AC LIQ (manufactured by HUNTSMAN) as a fluorescent whitening agent, 1 g / L of TANAVOL-DAP (manufactured by TANATEX) as a dyeing accelerator, 1 g / L of Ultra MT110 (manufactured by Shitegama Chemical Co., Ltd.) as a pH adjuster, and 1% by weight of INVALONNA (manufactured by HUNTSMAN) as a leveling agent was used.

[0100] (2) The fabric subjected to the above (1) was dyed at 60°C for 60 minutes using the dye and chemical described later, and then washed with water, soap, and hot water (warm water of 40 to 50°C). In the dyeing, a dyeing solution containing 3 wt% of Remazol Luminus YELLOW FL (manufactured by Dystar), 40 g / L of sodium sulfate, and 15 g / L of soda ash (sodium carbonate) was used as a reactive dye.

[0101] (3) The fabric subjected to the above (2) was disperse-dyed at 98°C for 15 minutes using dyes and chemicals described later, and then washed with water, soap, and hot water (warm water at 40 to 50°C). In the dyeing, a dyeing solution containing 0.1 wt% of Terasil Flavine 10GFF (manufactured by Dystar) as a disperse dye, 2 g / L of TANAVOL-DAP (manufactured by TANATEX) as a dyeing accelerator, 1 g / L of acetic acid, and 1 g / L of Nicca Sunsolt 7000 (manufactured by Nikka Chemical Co., Ltd.) and 1 g / L of Nicca Sunsolt RM3406 (manufactured by Nikka Chemical Co., Ltd.) as a dispersing and leveling agent was used.

[0102] (Example 2)

[0103] A fabric (weight per unit area: 5.7 oz / yd) was obtained in the same manner as in Example 1 except that the acrylic fiber of Production Example 2 was changed to 41 wt%, the lyocell fiber was changed to 35 wt%, and the aromatic polyamide fiber was changed to 24 wt%. 2 ).

[0104] (Comparative Example 1)

[0105] In Comparative Example 1, a fabric (weight per unit area: 5.7 oz / yd) was obtained in the same manner as in Example 1 except that the fluorescent whitening agent Uvitex AC LIQ (manufactured by HUNTSMAN) was not used in the dyeing step (1) and the dyeing steps (2) and (3) were not performed. 2 ).

[0106] (Comparative Example 2)

[0107] In Comparative Example 2, a fabric (weight per unit area: 5.7 oz / yd) was obtained in the same manner as in Example 1 except that the fluorescent whitening agent Uvitex AC LIQ (manufactured by HUNTSMAN) was not used in the dyeing step (1) and the dyeing step (3) was not performed. 2 ).

[0108] (Comparative Example 3)

[0109] In Comparative Example 3, a fabric (weight per unit area: 5.7 oz / yd) was obtained in the same manner as in Comparative Example 1 except that bleaching was performed using the following reagent before the dyeing step (1). 2 In the bleaching, as a fluorescent bleaching agent, a bleaching liquid containing Nichilon White WX Liquid (manufactured by Niksei Chemicals Co., Ltd.): 2 wt%, acetic acid: 1 g / L, Sol-Sin SK-F (manufactured by Niksei Chemicals Co., Ltd., a scouring agent): 1 wt%, sodium chlorite: 5 w / v%, sodium nitrate: 3 wt%, and sodium thiosulfate: 2 g / L was used.

[0110] (Comparative Example 4)

[0111] A fabric (weight per unit area: 5.7 oz / yd) was obtained in the same manner as in Example 1 except that 100 wt % of the acrylic fiber of Production Example 1 was used. 2 ).

[0112] Table 2 below shows the types and blending amounts of fibers in the fabrics of Examples and Comparative Examples.

[0113] The visibility, arc resistance, and friction fastness of the fabrics of Examples and Comparative Examples were measured and evaluated as described above, and the results are shown in Table 3 below.

[0114] Table 1

[0115]

[0116] Table 2

[0117]

[0118] Table 3

[0119]

[0120] As shown in Table 3, it was found that the fabrics of the examples subjected to three types of dyeing had high visibility and arc resistance, while the fabrics of Comparative Examples 1 to 3 had poor visibility after the light resistance test, and the fabric of Comparative Example 4 had poor arc resistance. In addition, it was found that the friction fastness of the fabrics of the examples was also improved.

[0121] The present invention is not particularly limited, and may include, for example, one or more of the following embodiments.

[0122] [1] A fabric comprising acrylic fiber A and cellulosic fiber, characterized in that:

[0123] Acrylic fiber A contains an infrared absorber inside the fiber.

[0124] The fabric is dyed with at least a cationic dye, a reactive dye and a disperse dye, and the cationic dye, the reactive dye and the disperse dye are all yellow fluorescent dyes.

[0125] [2] The fabric according to [1] above, wherein the acrylic fiber A contains an infrared absorber in an amount of 1% by weight or more and 30% by weight or less based on the total weight of the acrylic fiber A.

[0126] [3] The fabric according to [1] or [2], wherein the acrylic fiber A further contains a flame retardant.

[0127] [4] The fabric according to any one of [1] to [3], wherein the acrylic fiber A further contains a light diffusing reflective substance.

[0128] [5] The fabric according to any one of [1] to [4], wherein the weight per unit area of ​​the fabric is 6.5 oz / yd 2 When the following conditions are met, the ATPV measured based on ASTM F1959 / F1959M-12 (Standard Test Method for Determining the Arc Rating of Materials for Clothing) is 8 cal / cm 2 above.

[0129] [6] The fabric according to any one of [1] to [5], wherein the fabric satisfies the standards of 5.1 Requirements for color in ISO 20471:2013 and 5.2 Requirements for color after a xenon light fastness test in ISO 20471:2013.

[0130] [7] The fabric according to any one of [1] to [6], wherein the infrared absorber is a tin oxide compound.

[0131] [8] The fabric according to any one of [1] to [7], wherein the acrylic fiber A is contained in an amount of 30% by weight or more and 70% by weight or less based on the total weight of the fabric.

[0132] [9] The fabric according to any one of [1] to [8], wherein the cellulosic fibers are contained in an amount of 30% by weight or more and 65% by weight or less based on the total weight of the fabric.

[0133]

[10] The fabric according to any one of [1] to [7], further comprising aromatic polyamide fibers in an amount of 5% by weight or more and 30% by weight or less relative to the total weight of the fabric.

[0134]

[11] A clothing material characterized by comprising the fabric described in any one of [1] to

[10] .

[0135]

[12] A method for producing a fabric, the method for producing a fabric according to any one of [1] to

[10] , wherein:

[0136] The fabric containing acrylic fiber A and cellulose fiber is dyed by using cationic dye, reactive dye and disperse dye, and the cationic dye, reactive dye and disperse dye are all yellow fluorescent dyes.

Claims

1. A cloth, characterized in that: A cloth containing acrylic fiber A and cellulose fiber, Acrylic fiber A contains an infrared absorber inside the fiber. The fabric is dyed with at least three dyes, namely, a cationic dye, a reactive dye and a disperse dye, and the cationic dye, the reactive dye and the disperse dye are all yellow fluorescent dyes.

2. The fabric according to claim 1, wherein The acrylic fiber A contains an infrared absorber in an amount of 1% by weight or more and 30% by weight or less based on the total weight of the acrylic fiber A.

3. The fabric according to claim 1 or 2, wherein The acrylic fiber A further contains a flame retardant.

4. The fabric according to claim 1 or 2, wherein The acrylic fiber A further contains a light diffusing and reflecting substance.

5. The fabric according to claim 1 or 2, wherein The weight per unit area of ​​the fabric is 6.5 oz / yd 2 When the temperature is below 100 °C, the ATPV measured based on ASTM F1959 / F1959M-12 is 8 cal / cm 2 above.

6. The fabric according to claim 1 or 2, wherein: The fabric satisfies the requirements for color in 5.1 of ISO 20471:2013 and the requirements for color after a xenon light fastness test in 5.2 of ISO 20471:2013.

7. The fabric according to claim 1 or 2, wherein: The infrared absorber includes one or more selected from the group consisting of antimony-doped tin oxide, indium tin oxide, niobium-doped tin oxide, phosphorus-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide supported on a titanium oxide substrate, iron-doped titanium oxide, carbon-doped titanium oxide, fluorine-doped titanium oxide, nitrogen-doped titanium oxide, aluminum-doped zinc oxide and antimony-doped zinc oxide.

8. The fabric according to claim 1 or 2, wherein: The infrared absorber is a tin oxide compound.

9. The fabric according to claim 1 or 2, wherein: The acrylic fiber A is contained in an amount of 30% by weight or more and 70% by weight or less based on the total weight of the cloth.

10. The fabric according to claim 1 or 2, wherein: The cellulosic fibers are contained in an amount of 30% by weight or more and 65% by weight or less based on the total weight of the fabric.

11. The fabric according to claim 1 or 2, wherein: The fabric further contains aromatic polyamide fibers in an amount of 5% by weight or more and 30% by weight or less based on the total weight of the fabric.

12. The fabric according to claim 1 or 2, wherein: The fabric has a rubbing fastness of grade 4.5 or higher in a dry test measured according to the rubbing fastness test method specified in JIS L0849.

13. The fabric according to claim 1 or 2, wherein: The fabric has a rubbing fastness of grade 3.5 or higher in a wet test measured according to the rubbing fastness test method specified in JIS L0849.

14. A clothing material, characterized in that: A fabric comprising the fabric according to any one of claims 1 to 13.

15. A method for producing a fabric, the method for producing a fabric according to any one of claims 1 to 13, wherein: The cloth containing acrylic fiber A and cellulose fiber is dyed with three dyes, namely, cationic dye, reactive dye and disperse dye, all of which are yellow fluorescent dyes.

Citation Information

Patent Citations

  • Flame-retardant fabrics and garments made therefrom

    JP2010502849A

  • Arc resistant acrylic fiber, fabric for arc-protective clothing, and arc protective clothing

    WO2016111116A1

  • Arc resistant acrylic fiber, fabric for arc-protective clothing, and arc protective clothing

    CN107109709A

  • High-visibility flame-retardant acrylic knitted blended fabric

    CN111534909A